Effects of different preceding crops on soil properties and rhizosphere microbial community of sugar beet - Li, Yinghao; Yuan, Chunliu; Huang, Chunyan; Li, Zhi; Ren, Huimin; Zhang, Peng; Jian, Caiyuan; Han, Kang; Kong, Dejuan; Wang, Zhenzhen; Guo, Xiaoxia; Tian, Lu (Frontiers in Plant Science, 2025)
A significant challenge in sugar beet cultivation is the issue of continuous cropping cycles. The implementation of preceding crop cultivation has emerged as an effective strategy to mitigate the problems associated with continuous cropping systems. This study investigates how different preceding crops influence soil properties, microbial diversity, and community structure in the sugar beet rhizosphere, thereby establishing a theoretical foundation for addressing continuous cropping obstacles in sugar beet production. This study utilized a field experiment with four distinct preceding crop treatments-potato, oat, corn, and sunflower-prior to sugar beet cultivation. Subsequent analyses focused on sugar beet growth performance, soil chemical properties, and shifts in microbial community structure. The findings demonstrate that preceding crops significantly alter nutrient availability in sugar beet rhizosphere soil, microbial diversity, and overall crop productivity. Specifically, oat and potato stubbles substantially enhanced soil organic matter content, available nitrogen, phosphorus, and potassium levels, along with increased activities of alkaline phosphatase, urease, and sucrase, ultimately promoting sugar beet growth. Sunflower stubble exhibited distinct effects, notably increasing bacterial diversity while reducing fungal diversity. Across all treatments, the dominant bacterial phyla in the sugar beet rhizosphere were Firmicutes and Acidobacteria, whereas Ascomycota and Mortierellomycota prevailed among fungal communities. Importantly, sunflower stubble exerted the most pronounced influence on the relative abundance of these dominant bacterial and fungal phyla.